Actin cytoskeleton reorganization by the tyrosine kinase Syk regulates Fcγ receptor responsiveness by increasing its lateral mobility and clustering - Jaumouillé, Valentin (2014)
Clustering of immunoreceptors upon association with multivalent ligands triggers important responses including phagocytosis, secretion of cytokines and production of immunoglobulins. We applied single-molecule detection and tracking methods to study the factors that control the mobility and clustering of phagocytic Fcγ receptors (FcγR). While in resting macrophages the receptors exist as monomers, two distinct populations were discernible based on their mobility: some diffuse by apparent free motion, while others are confined within sub-micron boundaries that reduce the frequency of spontaneous collisions. Src-family and Syk kinases determine the structure of the actin cytoskeleton, which is fenestrated, accounting for the heterogeneous diffusion of the FcγR. Stimulation of these kinases during phagocytosis induces reorganisation of the cytoskeleton both locally and distally in a manner that alters receptor mobility and clustering, generating a feedback loop that facilitates engagement of FcγR at the tip of pseudopods, directing the progression of phagocytosis.